Evaluation of prevalence and predisposing factors of gingival recession in non-medical professional students in Nellore district, Andhra Pradesh: A cross-sectional study - Dhishann Babu Paturu; Sri Chandana Tanguturi; Vijay Kumar Chava; Sreenivas Nagarakanti (Wolters Kluwer Medknow Publications, 2016)
Introduction: Gingival recession is a common esthetic and undesirable problem that causes distress among individuals of all ages throughout the world. Identifying and diagnosing such a common clinical entity at an early stage, especially in young population groups, help them to restrict its progression through preventive methods. Aim: To evaluate the prevalence of gingival recession and role of various predisposing factors in nonmedical professional students in Nellore district. Materials and Methods: A cross-sectional study was carried out on a sample of 1079 engineering students. The subjects were interviewed for personal habits and examined for intraoral distribution of gingival recession and its various predisposing factors. The data obtained were statistically analyzed using Chi-square test and Phi and Cramer's V coefficient. Results: The prevalence of gingival recession was 24.29% of the studied population. The prevalence of gingival recession is higher in males (68.7%) than in females (31.3%). There was a significant association (P < 0.05) between gingival recession and width of attached gingiva, tooth malposition, type of frenal attachments, simplified oral hygiene index, type of brush, and fremitus test. Conclusion: The prevalence of gingival recession was higher in males than in females with varying predisposing factors. Emphasis should be made on awareness of various periodontal problems and preventive methods to avoid future tooth loss in younger adults.